Sensibilidade de plantas cultivadas ao dicamba e 2,4-D aplicados em doses comerciais e subdoses - Boteon, Beatriz Fogolari (Universidade Federal de São Carlos, 2022)
The development of crops resistant to dicamba and 2,4-D may reflect the intensive use of these herbicides in agricultural areas, including close to susceptible species. Therefore, the objective of this work was to evaluate the sensitivity of bean, peanut and cotton crops to different doses of dicamba and 2,4-D. The experiments were isolated and conducted in a greenhouse in a completely randomized design with four replications in a 2 x 8 +1 factorial, with two herbicides, 8 doses and a control without application. Bean, cotton and peanut plants were submitted to different doses of 2,4-D with 670 (commercial dose); 335; 167.5; 83.75; 41.87; 20.93; 10.46 and 5.23 g a.i. ha-1 and dicamba at doses 560 (commercial dose); 280 ;140; 70; 35 ;17.5; 8.75 and 4.37 g a.i. ha-1 when they had the second pair of true leaves. Phytotoxicity assessments were performed at 5, 10 and 15 days after application (DDA). At 15 DAA, the leaf area of ​​the plants was evaluated and the dry biomass of the aerial part was removed. In the cotton crop applied with 2,4-D up to the dose of 83.75 g a.i. ha-1 showed 80%, from 20.93 g a.i. ha-1, it did not present phytotoxicity. For the bean crop sprayed with 2,4-D, doses of 670 and 335 g a.i. ha-1 caused the highest levels of injury (up to 95%). From the dose of 167.5 g a.i. ha-1 they also caused injuries, even at the lowest dose of 5.23 g a.i. ha-1 . Plants sprayed with dicamba caused plant death at doses 560; 280; 140; 70; 35 g a.i. ha-1 , and even at the lowest doses (17.5; 8.75 and 4.37 g a.i. ha-1 ) showed 80% to 70% phytotoxicity, respectively. In peanut, the dose of 670 g a.i. ha-1 of 2,4-D showed 60% phytotoxicity, being the highest. The doses of 20.93; 10.46 and 5.23 g a.i. ha-1 did not show any phytotoxicity. Peanut plants sprayed with dicamba showed up to 70% at the dose of 70 g a.i. ha1 . Only the dose of 4.37 g a.i. ha-1 did not present any injury. It is necessary to pay attention to the use of these herbicides when applied close to the crops, because in sub-doses toxic effects were verified in the plants.
Sensitivity of cultivated plants to dicamba and 2,4-D applied in commercial doses and subdoses
Keywords: Contaminação; Herbicidas hormonais; Fitotoxicidade; Contamination; Phytotoxicity; Hormonal herbicides; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA